Effect of overweight and obesity on voluntary breath-holding time in university students - Cortes-Romero, Celso Enrique; Luna-Alvarado, Luis Antonio; Santos-Díaz, Belén (Horizonte Sanitario, 2025)
Objective: To evaluate the effect of overweight and obesity on voluntary breath-hold time in university students Materials and Methods: A cross-sectional, quantitative study was conducted. The study sample consisted of 97 second-year medical students from a public university in Mexico, in whom voluntary breath-hold time (BHT) was determined. The study sample was classified using percentage of body fat (%BF), body mass index (BMI), and waist-to-hip ratio (WHR). Spearman’s correlation coefficient was used to establish the correlation between the scores of the variables. A statistical significance level of p<0.05 was considered. Results: 42.2% (n=41) of the participants were male and 57.7% (n=56) were female, with an average age of 19.88±1.14 years. For the total sample, the average BHT was 30.5±8.37 seconds. Women had a lower BHT, although no statistical difference was found in the average BHT between the sexes. Additionally, compared to normal-weight subjects, those in the elevated category of each anthropometric parameter showed a decrease in BHT duration. The decrease in BHT was statistically significant between the BMI categories (p=0.013) and the WHR categories (p=0.020). Spearman’s correlation coefficient showed a negative and significant relationship between BHT and percentage of body fat (rho=-0.257; p=0.011) and waist-to-hip ratio (rho=-0.261; p=0.010). The score between BHT and BMI was also negative but not significant (rho=-0.183; p=0.073). Conclusions: The determination of overweight and obesity through percentage of body fat, body mass index, and waist-to-hip ratio, is related to a shorter duration of voluntary breath-hold time in university students. Keywords: Apnea; University students; Obesity